REPORTS ON EMERGENCY ASSISTANCE FOR PATIENTS WITH INFECTIOUS DISEASES DURING THE PANDEMIC PERIOD OF COVID 19 - Martins Gonçalves , Maria Edina; Alves Pereira, Ageu; Battanoli Amed , Flora; Lima de Oliveira , Luciana; Monteiro Alves, Raquel; Colares da Silva , Jaíne; Menezes , Ingrid dos Santos; Teixeira de Sousa Marinho, Daiane; Gomes Farias, Suzete; Portela de Azevedo , Arimateia (Revista Feridas, 2023)
Introduction: One of the challenges for those who work in emergency services are the risks of exposure, especially when the service is specialized in caring for patients with infectious and contagious diseases. Objective: To trace qualitative data through direct observations of the records and also the reports of professionals regarding the experiences and experiences in an emergency care service for patients with infectious and contagious diseases treated at the reference hospital during the peak of the Coravirus pandemic and the difficulties caused by the pandemic moment. Methodology: Descriptive, qualitative, observational study. Results: Many reports indicated emotional instability among the servers: “this pandemic has changed our emotional behavior because, due to not having much understanding about this new pathogen and due to the speed of contagion and lethality, it is clear that the psychological has been severely affected of the whole team”. Other examples of emotional instability recorded were: “the entire team remains on constant alert regarding the frequent use of PPE due to the imminent risk of biological contamination, but today a patient was admitted with bleeding and who was known to already have an infectious disease and who had dyspnea and cough, and the amount of PPE in the sector was sufficient for a twelve-hour shift. However, it was evident on everyone’s face a facial expression of unease ". Conclusion: Working in the emergency department of a hospital that is a reference for patients with infectious and contagious diseases means accumulating, at each shift, the psychological burden of the real risk of being exposed to biological material.